Antioxidant Activity of Endophytic Fungi Isolated from Turmeric Flowers - Eris Septiana; Yadi Yadi; Partomuan Simanjuntak (Biosaintifika: Journal of Biology & Biology Education, 2020)
Antioxidants are compounds needed by the body to fight free radicals that can cause adverse effects on health. All parts of turmeric plant have antioxidant activity, so does the flower. It is thought that the endophytic fungi from turmeric flowers also have antioxidant activity and no studies have reported it yet. The purpose of this study was to study the antioxidant activity of single and mixed cultures of endophytic fungi isolated from turmeric flowers. In vitro antioxidant activity assay was conducted using the DDPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging method by measuring its absorption using a UV-Vis spectrophotometer at a wavelength of 517 nm. The extract of single and mixed cultures of endophytic fungi isolated from turmeric flowers showed antioxidant activity. The combination of fungal cultures can increase the antioxidant activity of a single culture. This study is the first to report that the combination of endophytic fungi from turmeric flowers can increase its antioxidant activity. Therefore, the presence of the endophytic fungi in turmeric flowers that have antioxidant activity can provide additional information so that the utilization of turmeric flowers as a source of natural antioxidants will increase.